2015
DOI: 10.3390/nu7095331
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Copper Status and Working Memory in Schoolchildren

Abstract: Trace elements such as copper are essential micronutrients. Traditionally, copper has been studied in the context of micronutrient deficiencies. Recent studies in both animals and humans, however, have revealed that elevated blood copper can also have adverse effects on cognitive function since free copper can cross the blood-brain barrier and subsequently impose oxidative stress to neuronal cells. However, most of these human studies were conducted in adult populations with and without cognitive decline, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…Consistent with our results, a recent study has reported a significant association between high copper levels in blood and poorer cognitive performance in normal school children (Zhou et al. ).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our results, a recent study has reported a significant association between high copper levels in blood and poorer cognitive performance in normal school children (Zhou et al. ).…”
Section: Discussionsupporting
confidence: 93%
“…Such effects can be very significant, but now their identification is difficult. Because some participants of the CTS are still unknown while some copper-binding proteins are ‘moonlighting’ and their activities depend on the copper level (e.g., Cp, CTR1, ATOX1, and COMMD1) [ 36 , 167 , 168 , 169 , 170 , 171 ], we may suggest that the differences between breastmilk and infant formula with respect to copper concentrations and copper ‘packaging’ by the Cp protein may be one of the factors that contribute to the negative effects of bottle feeding on the cognitive abilities of children [ 172 , 173 ].…”
Section: Resultsmentioning
confidence: 99%
“…Because some participants of CTS are still unknown while some copper-binding proteins are 'moonlighting' and their activities dependent on copper level (e.g. Cp, CTR1, ATOX1, COMMD1) [31,[151][152][153][154][155], we may suggest that the differences between breastmilk and infant formulas with respect to copper concentrations and copper 'packaging' by the Cp protein may be one of the factors that contribute to the negative effects of bottle feeding on the cognitive abilities of children [156,157].…”
Section: Resultsmentioning
confidence: 99%